Adsorption of Deta during Dynamic Conditions of Flotation in the Depression of Pyrrhotite - Sadan Kelebek; Peter F. Wells; S. O. Fekete; Gerhard W. Heinrich (Canadian Institute of Mining, Metallurgy and Petroleum, 1995)
"For many years, rejection of pyrrhotite at the milling stage has been a viable method for sulphur dioxide abatement. Pyrrhotite rejection options have included the use of selective pyrrhotite depressants in flotation; a depressant which has recently come into use is diethylenetriamine (DETA). This reagent has been the subject of recent research and development efforts in the processing of nickel-copper sulphide ores.In the present study, adsorption trends for DETA have been monitored under the dynamic conditions of flotation using a spectrophotometric method which has been adopted for this purpose at Falconbridge Limited. The results indicate that the adsorption of DETA is quite fast and in the majority of cases, accounts for the disappearance of 75-95 % of this reagent from pulp's liquid phase. The adsorption decreases linearly with an increase in the DET A dosage from 100 git to 600 git. The tailings produced in flotation tests were subjected to washing with deionized water at 60 °C to examine the desorption of DET A. These results indicate that the amount desorbed increases with increasing DETA dosage used during flotation but is less than 7 per cent of that adsorbed. It was found that adsorption of DETA alone, even at relatively high levels, does not always cause depression of pyrrhotite. A new combination of reagents identified in the metallurgical laboratories of Falconbridge Limited utilizes sulphur dioxide with DETA. These reagents together are capable of efficient depression of pyrrhotite on a consistent basis."